Colonic Wall Thickening Reported in Abdominal CT: Does It Always Imply Malignancy?. (22nd December 2019) - Akbas, A.; Bakir, H.; Dasiran, M. F.; Dagmura, H.; Daldal, E.; Ozsoy, Z.; Ozmen, Z.; Demir, O.; Okan, I.
Abstract : Aim/Background . Early diagnosis of patients with colon cancer is one of the most important parameters affecting the survival of patients. In this study, we aimed to examine the effect of the age, hemoglobin (Hb), albumin, neutrophil lymphocyte ratio (NLR), thrombocyte lymphocyte ratio (PLR), and mean platelet values (MPV) on the separation of benign and malignant diseases in patients with suspected colon wall thickness (CWT) observed in abdominal computed tomography (CT) examination. Method . The study included 116 patients between the ages of 18 and 95 who had CT examination where the colon wall could be evaluated and who also had colonoscopy. Patients suspected for CWT in CT with difficulties in differential diagnosis were divided into two groups according to colonoscopic-histopathological evaluations. Normal or benign pathological causes were included in the first group, while malignant causes constituted the second group. Whether the two groups differed in terms of CWT, Hb, age, albumin, NLR, PLR, and MPV values was investigated with descriptive statistics. Results . One hundred and sixteen patients (74 males, 42 females) with CT examinations and colonoscopic sampling were included in the study. After colonoscopic and histopathological evaluations, there were 64 cases in the first group and 52 in the second group. According to the results of the univariate analysis and multivariate logistic regression, CWT, Hb, NLR, and MPV were identified to be independent variables for determining colon cancer. Conclusion . A combined evaluation of Hb, NLR, and MPV values in patients with CWT in abdominal CT examination may contribute to the separation of benign and malignant pathologies.